2006
DOI: 10.1111/j.1525-142x.2006.05073.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and divergence in the AGAMOUS subfamily of MADS‐box genes: evidence of independent sub‐ and neofunctionalization events

Abstract: The MADS-box gene AGAMOUS (AG) plays a key role in determining floral meristem and organ identities. We identified three AG homologs, EScaAG1, EScaAG2, and EScaAGL11 from the basal eudicot Eschscholzia californica (California poppy). Phylogenetic analyses indicate that EScaAG1 and EScaAG2 are recent paralogs within the AG clade, independent of the duplication in ancestral core eudicots that gave rise to the euAG and PLENA (PLE) orthologs. EScaAGL11 is basal to core eudicot AGL11 orthologs in a clade representi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
158
0
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(175 citation statements)
references
References 101 publications
(212 reference statements)
10
158
0
7
Order By: Relevance
“…A duplication event in the AG lineage at the base of the angiosperm radiation has led to the presence of two or more AG clade genes in most higher eudicot species (Kramer et al, 2004;Zahn et al, 2006). Here, we show that the petunia C-function is encoded by two genes, PMADS3 and FBP6, in a largely redundant fashion: We observed only mild phenotypes in the single loss-of-function lines, but fbp6 PMADS3-RNAi plants display a complete loss of reproductive organ identity and of determinacy.…”
Section: Discussion the C-function In Petunia Is Redundantly Encoded mentioning
confidence: 99%
See 1 more Smart Citation
“…A duplication event in the AG lineage at the base of the angiosperm radiation has led to the presence of two or more AG clade genes in most higher eudicot species (Kramer et al, 2004;Zahn et al, 2006). Here, we show that the petunia C-function is encoded by two genes, PMADS3 and FBP6, in a largely redundant fashion: We observed only mild phenotypes in the single loss-of-function lines, but fbp6 PMADS3-RNAi plants display a complete loss of reproductive organ identity and of determinacy.…”
Section: Discussion the C-function In Petunia Is Redundantly Encoded mentioning
confidence: 99%
“…The C-and D-lineage genes together compose the AGAMOUS (AG) subfamily within the MADS box transcription factor family. This subfamily can be divided into two clades: the C-clade (which is further divided into two subclades; the euAG-and the PLENA-subclade) and the D-clade (Colombo et al, 1995;Kramer et al, 2004;Zahn et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…MADS3 and MADS58 fall into the AG lineage, whereas MADS13 and MADS21 are AGL11 lineage genes (Kramer et al, 2004;Yamaguchi et al, 2006;Dreni et al, 2007). Although Zahn et al (2006) placed MADS13 in the AG lineage, other phylogenetic analyses, gene structure, and specific amino acid residues strongly suggest that MADS13 belongs to the AGL11 lineage (Kramer et al, 2004;Dreni et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis, four genes, AG, SHATTERPROOF1 (SHP1), SHP2, and SEEDSTICK (STK; previously known as AGL11), form the AG monophyletic subfamily within the MADS box gene phylogeny (Parenicová et al, 2003;Kramer et al, 2004;Zahn et al, 2006). Analysis of the evolutionary history of gene duplications showed that the SHP1 and SHP2 genes are the products of a recent duplication event, which probably occurred after the divergence of rosid and asterid eudicots (Vision et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation